Teori Kritik Frye dalam Memahami Hadis Perintah Salat di BanÄ« Quraizah pada Kitab Kompilasi Hadis - Fatihunnada, Fatihunnada (Institut Agama Islam Negeri (IAIN) Curup, 2023)
Frye's Critical Theory in Understanding the Hadith of Prayer Commands in BanÄ« Quraizah in the Hadith Compilation BookThe discussion on the understanding of hadith in the two textual and contextual camps is very broad, but has not yet touched on the object of the hadith compilation books. The compilation of hadiths can be seen not only as a work that collects the hadiths of the Prophet, but also as a pattern of understanding hadiths by looking at the pattern of placement of the hadiths of the Prophet in certain chapters that the authors of the hadith compilations deem appropriate based on the text or context. This article discusses the hadith of the Prophet prohibiting his companions from praying, unless they have arrived in the BanÄ« Quraiza area from the aspect of the companions' understanding of this Prophet's order, some of them pray at Bani Quraiza according to the Prophet's orders and some of them pray on the way for fear of delays in time. This article uses Frye's theory with centripetal, centrifugal, and literary myth meanings which are used to analyze the reading/understanding of the text with a focus on the near or far point of the text, as well as the meanings conveyed by the hadith compilers in TabwÄ«b hadis. With the Fryeâ€™s theory approach, it can be emphasized that the hadith compilers have made efforts to understand the hadith with the TabwÄ«b of this hadith in different chapters. Al-BukhÄrÄ«, Muslim, Ibn á¸¤ibbÄn, al-BagawÄ«, al-á¹¬abrÄnÄ«, al-BaihaqÄ«, AbÅ« YaÊ»lÄ, AbÅ« 'AwwÄnah, 'Abd al-RazzÄq, and al-á¸¤Äkim wrote this hadith on an unrelated discussion or theme (TabwÄ«b) on the understanding of the companions of the Prophet's orders. Muslim and Ibn á¸¤ibbÄn place this hadith on the discussion of the companions' obedience to the Prophet's orders, while al-BaihaqÄ« and AbÅ« 'AwwÄnah place this hadith on the contextual understanding of the companions of the Prophet's orders by considering the provisions of prayer times.